Multi-Parametric Magnetic Resonance Imaging (MpMRI) Based Prostate Imaging and Reporting Archiving Data System (PIRADS): Utility in Improving Cancer Detection, Localization and Characterization - Alpajaro, Sigfred Ian; Letran, Jason (Philippine Journal of Urology, 2020)
The Prostate Imaging and Reporting Archiving Data System (PI-RADS) uti-lizes multiparametric MRI (mpMRI), allowing for lesion characterization as an aid for prostate cancer detection. Objectives: This study aimed to determine the sensitivity of PI-RADS in de-tecting clinically significant prostate adenocarcinoma on biopsy, and correlating it with Gleason score. Materials and Methods: Thirty-two (32) consecutive patients suspected with prostate cancer underwent mpMRI between July 2014 to July 2015. A single radiologist reviewed the mpMRI and assigned PIRADS scores to lesions detected. Using cognitive technique, prostate biopsy was done via transperineal approach. Regions of interest were initially sampled, followed by areas on systematic sector based on established template. Histopathologic interpretations were done by a single group of pathologists. Results: The mean age of the study population was 67 years. The mean prostate size was 50.4grams, and the mean PSA was 12.1 ng/dl. Forty-five (45) lesions were detected by mpMRI and assigned a PIRADS score of 3,4, and 5. Overall, 31/45 (68.8%) lesions described as PI-RADS 3,4, or 5, turned out to be prostate carcinoma. Of those with iden-tified MRI lesions, 3/9 (33.3%) PIRADS 3, 10/17 (58.7%) PIRADS 4, and 18/19 (94.7%) PIRADS 5 were positive for malignancy respectively. The overall mean PI-RADS 3,4 and 5 lesions score was 4.48, and mean Gleason grade was 7.61. Using Kendall rank correlation, the tau coefficient was 0.3266 (p-value = .009), consistent with a positive correlation between PI-RADS score and Gleason grade. Conclusions: Multiparametric MRI combined with the use of PI-RADS help increase the detection and accuracy in diagnosis of clinically significant prostate cancer. There is cor-relation between PIRADS and Gleason grade. It's significance lies in potentially pre-venting over diagnosis of indolent, low grade cancers by preventing unnecessary biop-sies while allowing clinically significant cancers to be appropriately managed.